ANTIBACTERIAL POTENTIAL OF GREEN MENIRAN (PHYLLANTHUS NIRURI L.) LEAVES EXTRACT AGAINST STAPHYLOCOCCUS AUREUS ATCC25923 : AN IN VITRO STUDY - Tara Raudhatul Jannah; Iswadi Iswadi; Samingan Samingan; Suhartono Suhartono; Andi Ulfa Tenri Pada (Universitas Islam Negeri Ar-Raniry, 2024)
Green meniran (Phyllanthus niruri L.) contains secondary metabolites which are useful as antibacterials. This plant could be a candidate for a solution to the phenomenon of antibiotic resistance, one of which is the Staphylococcus aureus bacteria. S. aureus is a Gram-positive bacteria that causes purulent infections and commonly affects the respiratory organs, skin and digestive tract. The purpose of this study was to determine the effectiveness the extract of this plant as an antibacterial against S. aureus, the most effective concentration of the extract in inhibiting this bacteria and also the efficiency of the extract produced. The method used was experimental with a quantitative approach using a non-factorial Completely Randomized Design (CRD) consisting of 7 treatments with 3 replications each. Data analysis was performed using the Kruskal Wallis non-parametric test with a significance level of 0.05 and the Dunnet follow-up test. The results of this study indicated there was 22.5% extraction efficiency in this study and had an antibacterial effect on S. aureus in vitro. In this case, a concentration of 80% was determined as the most effective concentration in inhibiting the growth of S. aureus bacteria with an average diameter of the inhibition zone of 24.27 mm.